The efficacy of methanolic extract of Swietenia mahagoni Jacq. (Meliaceae) and a commercial insecticide against laboratory and field strains of Aedes aegypti (Linn.) and their impact on its predator Toxorhnchites splendens. (January 2021) - Vasantha-Srinivasan, Prabhakaran; Karthi, Sengodan; Ganesan, Raja; Senthil-Nathan, Sengottayan; Krutmuang, Patcharin; Chellappandian, Muthiah; Radhakrishnan, Narayanaswamy; Ponsankar, Athirstam; Karthick, Kalvikkarasan; Nelofer, Abdul-Raheem
Abstract: Comparative baseline toxicity of chemical pesticides Temephos, along with the crude extracts of Swietenia mahagoni Jacq. (Meliaceae) (Mx-Sm) against the Laboratory strains (LS) and Wild Strains (WS) of Aedes aegypti Linn. and their non-target screening against the aquatic predator was analyzed. The larval mortality was significant in Temephos (0.5 ppm-93.5%) and Mx-Sm (300 ppm-92.10%) and statistically altered with control. Despite this, the larval mortality is relatively higher in LS than WS treated with Temephos in all the treated instars. Both strains LS and WS displayed stable mortality rate across all the instars while treated with Mx-Sm (300 ppm). The sub-lethal concentration of Mx-Sm (205 ppm) showed no significant differences in the level of α- and β-carboxylesterase. But, there is a significant difference observed between both strains treated with Temephos (0.35 ppm). Similar trends were observed in the GST and CYP450 levels, as the enzyme ratio gets uplifted prominently in the WS compared to the LS in Temephos treatment. Whereas the enzyme regulation up-lifted steadily in both LS and WS treated with Mx-Sm. The non-target screening of Mx-Sm and Temephos against the mosquito predator Toxorhynchites splendens revealed that the Mx-Sm was less toxic at the prominent dosage 1000 ppm as compared to Temephos (1 ppm). Thus the safety index recommends that Mx-Sm was a target-specific and suitable alternative for chemical pesticides. Graphical abstract: Image 1 Highlights: Temephos along with biorational crude extract of  Swietenia mahagoni  extract against laboratory and wild strains of dengue vector. The larval mortality is relatively higher in LS than WS treated with Temephos. The sub-lethal dosage of 205 ppm significantly reduced the enzyme level of carboxylesterase. The level of GST and CYP450s as the enzyme ratio gets uplifted in the different strains in Temephos treatment. The non-target screening against aquatic predator was harmless as compared to Temephos.